PERILAKU MAHASISWA ASAL PAPUA DALAM PROSES BELAJAR DI LINGKUNGAN KAMPUS UNIVERSITAS SAM RATULANGI MANADO - Cauna, Anselmus; Pratiknjo, Maria Heny; Deeng, Djefry (Universitas Sam Ratulangi, 2019)
The complexity of student life in higher education is generally oriented towards achieving the self-actualization they have in terms of establishing academic achievement. Student learning achievement is the result of assessment of learning activities that have been carried out and is a form of final formulation given by the lecturer to see students' abilities expressed in the form of symbols, numbers, letters or sentences that can reflect the results that have been achieved. Student learning achievement can be seen from the cumulative index (GPA) obtained by students.The problem that is of concern to researchers is the behavior of students from Papua in dealing with problems that often arise in the learning process, causing students from Papua to be willing to leave the lecture bench. From the description above, the researcher concludes that there are other possible causes that hinder the learning process of students in the Sam Ratulangi University campus environment, especially in the Faculty of Social and Political Sciences.This study aims to determine the behavior of students from Papua in the learning process in the Sam Ratulagi University of Manado campus environment. Research results show:Factors that caused the Behavior of Papuan Students in the Learning Process as much as 40% not continuing their studies in the Sam Ratulangi University Campus environment were internal factors and external factors. Internal factors include psychological factors and personal factors which include: Internal psychological factors include: Self-motivation, Perception, Attitude and belief. Personal internal factors include: Age, Occupation, Economic Condition, Personality, and Gender. While external factors include: culture, social class and family.Keywords: Student Behavior, learning process